Correlation between physical activity and sedentary behavior in students - Otávio Amaral de Andrade Leão; Tiago Silva dos Santos; Marcelo Cozzensa da Silva (Universidade de Fortaleza, 2018)
Objective: To evaluate the correlation between physical activity (PA) and sedentary behavior (SB) of Physical Education (PE) undergraduates over a year in the program. Methods: A quantitative and longitudinal study, involving all students of associates's degree (day and evening) and bachelor's degree programs of the Federal University of Pelotas (UFPel) in 2014 (n=115) and their follow-up in 2015. The first data collection occurred at the beginning of the first semester and the follow-up, after one year in the program. PA and SB were assessed by means of the long version of the International Physical Activity Questionnaire, and data analysis was performed using Pearson's correlation test. Results: The PA of the students presented a high median in the first and second analysis, and their SB showed a high mean in the baseline and in the follow-up. No correlation was evidenced between PA and SB at the baseline (r=-0.02). However, after one year, a weak but positive correlation was identified (r=0.12). Conclusion: The correlation between sedentary behavior and physical activity evaluated in both periods was weak, but a timid increase over a year was perceived.